Lessons learned from using an audience response system in a community setting for research data collection. Issue 4 (22nd March 2018) - Bryant‐Moore, Keneshia; Haynes, Tiffany; Kuo, Dennis Z.; Stewart, M. Kathryn; Yeary, Karen Hye‐Cheon Kim; Smith, Johnny; Turner, Jerome; Ounpraseuth, Songthip T.; Sullivan, Greer; McCoy, Stephanie; Hudson, Brittany; Harris, Kimberly
Abstract: Objectives: A community‐academic team implemented a study involving collection of quantitative data using a computer‐based audience response system (ARS) whereby community partners led data collection efforts. The team participated in a reflection exercise after the data collection to evaluate and identify best practices and lessons learned about the community partner‐led process. Design & Sample: The methods involved a qualitative research consultant who facilitated the reflection exercise that consisted of two focus groups—one academic and one community research team members. The consultant then conducted content analysis. Nine members participated in the focus groups. Results: The reflection identified the following themes: the positive aspects of the ARS; challenges to overcome; and recommendations for the future. Conclusion: The lessons learned here can help community‐academic research partnerships identify the best circumstances in which to use ARS for data collection and practical steps to aid in its success.